Emotional intelligence among Malaysian young adults in community college, Jitra - Tee, Ker Shin; Ahmad, Nor Aniza; Roslan, Samsilah; Che Hassan, Norlizah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
There is a rising tide of understanding among public, Emotional Intelligence (EI) researchers and psychologists that EI is the “missing piece” of education. Educators should give a serious consideration of infusing EI learning into the standard academic curriculum. Accordingly, transition to higher education is one of the major developmental challenges for young adults. The root causes of this challenge include management of emotions, adaption to new academic circumstance and establishment of healthy interpersonal relationship with others. In this regard, EI is said to be a protective factor for young adults, as it leads to a more effective coping and social relationship. Although the EI could have a positive impact on students’ development, there are just a few studies devoted to investigate EI among Malaysian young adults, particularly in Jitra. Thus, the study was to examine the level of EI among college students from four certificate programmes, including Automotive, Computer System and Support, Electrical Technology, and Draughtsman. In addition, the study also investigated the difference of the EI level between participants from four certificate programmes. Data collection occurred with cross sectional survey approach incorporating the Schutte Self-Report Emotional Intelligence Scale (SSREI). Samples of the research consisted of two hundred and twenty eight certificate students, with age range between 18 and 25 years old, from Bandar Darulaman Community College. The research revealed that 53.9% of students possessed medium level of EI, 43.4 % reported low level of EI and 2.6% scored highly in the EI assessment. Data analysis indicated that there were significant differences in EI among students from different programmes and majority of college students scored low in the aspect of emotional expression and appraisal of emotions in the self. In addition to academic knowledge and technical skills, this potentially represents Malaysian young adults need emotional and social skills to achieve their success in both academic and interpersonal context. As EI can be trained and educated, the implication of this study would be needed to formally establish online EI training and to provide concrete guidelines for EI practices in higher education institutes. Further research can be conducted to discover the influence of role expectation, gender, and cultural practices on EI among this population.